Existential threats to pastoralism in an arid environment: the fate of Gujii pastoralists in Southern Ethiopia - Mekuria Haleke Guye; Abiyot Legesse; Yimer Mohammed (Journal of Degraded and Mining Lands Management, 2023)
The pastoralists of Gujii have faced numerous risks, with their pastoralism system facing serious challenges. With the technically inconsistent and timely unmanaged interventions, several pastoral households are facing unreserved challenges. As a result, the future of pastoralists appears to be in great danger. The objective of this study is to investigate the ongoing challenges of Gujii pastoralism, as well as the fate of pastoralists in southern Ethiopia who are suffering from unrelenting drought. Ethiopian Meteorological Agency provided monthly rainfall and temperature data from 1986 to 2016. A household survey was conducted with 340 household heads randomly chosen from the study area to examine the challenges of the pastoralists have been facing. Moreover, a key informant interview and a focus group discussion were employed to collect qualitative data. Each watershed unit held one round of focus group discussions, with an average of 7-10 participants. The coefficient of variation (CV) was used to detect the temporal variability of seasonal rainfall and temperature. To detect trends, the Mann Kendall (MK) and Sen's slope estimator were used to determine the trends and magnitude of the change.  Political and tenure insecurity seriously affected the pastoral system in different ways. Autumn and spring had high variability in rainfall, with CV = 48.76% and 32.43%, respectively. Both winter and spring temperatures show a significant increase at (a = 0.1). Climate variability has made the already fragile pastoral households even more vulnerable. Pastoralist’s future would be difficult with all of these problems, and its resilience would be doubtful. As a result, in order to ensure the pastoral's long-term survivability, the government.